2005
DOI: 10.1055/s-2005-864847
|View full text |Cite
|
Sign up to set email alerts
|

Sural Nerve Harvest: Anatomy and Technique

Abstract: A minimally-invasive technique of sural nerve harvesting using an initial blunt tip harvesting device, combined with a recessed sharp cutting mechanism for final severance of the nerve, has been developed. Important surgical landmarks have been established, based on a review of the anatomy of the sural nerve. Harvesting is begun through a small incision at the level of the lateral malleolus, thereby identifying the nerve and inserting the nerve-harvesting device. An additional small incision, if needed, is pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 6 publications
0
25
0
Order By: Relevance
“…Sural nerve harvesting is not an innocuous procedure since it may result in sensory deficit on the lateral ankle, wound infection or neuroma. 20 In our series only 1 patient (2%) experienced wound infection and phantom pain in the distribution of the donor site.…”
Section: Discussionmentioning
confidence: 95%
“…Sural nerve harvesting is not an innocuous procedure since it may result in sensory deficit on the lateral ankle, wound infection or neuroma. 20 In our series only 1 patient (2%) experienced wound infection and phantom pain in the distribution of the donor site.…”
Section: Discussionmentioning
confidence: 95%
“…In this study, the mean of the SN was 11.3 cm and the distance from the point where MSCN pierced 16 The SN always appears with the small saphenous vein between the calcaneal tendon and the line that connects the lateral malleolus and the tendon of the peroneus longus muscle. 12,16 The present study identified the SN running with the saphenous vein.…”
Section: Discussionmentioning
confidence: 97%
“…In infants, this has an effect that should be considered because it reduces harm to the child by decreasing the heat loss caused by larger incisions; it involves less blood loss; it offers better cosmetic results and it also involves a lower likelihood of equinovarus contractures. 6,7 In the first cases, we had tried to use a zero-degree endoscope, but it was much more cumbersome than using a thirty-degree endoscope. Therefore, a thirty-degree cystoscopic lens was used for the procedure, but any short and thin endoscope can be used.…”
Section: Discussionmentioning
confidence: 99%
“…The classical sural harvesting techniques, which include a longitudinal incision from the ankle to the popliteal fossa or incisions in multiple steps (with transverse incisions), have the disadvantage of greater blood loss and large scars that may cause contractures and deformities of the equinovarus type. 6,7 The endoscopic technique was developed to minimize surgical trauma, decrease the skin incision size and, therefore, decrease the likelihood of lower limb deformities. [5][6][7] Endoscopic techniques have been widely used in the harvesting of the saphenous vein and the radial artery for vascular surgeries with the advantages of minimal scars and less postoperative complications, such as hypersensitivity of the skin, scars and infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation